The Relationship between Principal's Clinical Supervision and Work Environment on Vocational High School Teacher Performance (SMK) - Amirudin, Amirudin; Angelina, Syahda Litahna’a (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2024)
This study is motivated by the performance of teachers who have not been maximized in SMK in Losari, Brebes. so that there needs to be a more approach so that teacher performance becomes better. The aim of this study became to acquire an overview of: the relationship among principal supervision and the work environment of Vocational high school teachers in Losari, Brebes, the impact of principal supervision on the overall performance of Vocational high school teachers in Losari, Brebes Subdistrict, the influence of the work environment at the overall performance of Vocational high school teachers in Losari Brebes Subdistrict, the effect of principal supervision and work environment at the performance of Vocational high school teachers in Losari, Brebes Subdistrict. The method of studies uses a quantitative method, which means that each one information or data obtained is realized with numbers, and the analysis used is statistical analysis. With proportional random sampling approach, and taken as a sample of 110 human beings from a populace of 151 teachers. Results of the study all variables have been significantly related. And the conclusion of this examine is that the variables of principal clinical supervision and work environment have an effect of 57.3%, at the performance of vocational high school teachers in Losari, Brebes sub-district, while the remaining 42.7% is stimulated through different variables that aren't studied